Inter-daily variability in body composition among young men - Kutáč, Petr (Journal of physiological anthropology, 2015)
BACKGROUND: The present study analyses changes in body composition over the course of a working week. The purpose of the study is to identify the size of the changes in the observed parameters by means of typical error of measurement (TE) as the initial value for the interpretation of the detected changes in the repeated measurement in diagnostic practice. METHODS: The researched group consisted of 86 males, aged 21.4 ± 1.0 years. All the participants were free of any medical conditions. The measurement of each participant took place over 1 week from Monday till Friday, in the morning hours. Parameters measured: body mass (BM), total body water (TBW), and body fat (BF). The measurement employed two devices using the bioelectric impedance analysis. These devices were the analyzers Tanita BC 418 MA and Nutriguard MS. In order to assess the differences between the average values, the analysis of repeated measurements was used. To assess the material significance, eta squared was used. TE was used to express the size of the changes in the observed parameters. RESULTS: A statistically significant difference between the average values of the observed parameters was only detected when using the Tanita BC 418 MA analyzer. Based on the post-hoc tests, these differences in the average values were always detected on Monday and Friday. No material significance was proved, however. The highest TE values were also detected in measurements carried out on Monday and Friday. For BM, the value of TE was 0.6 kg, for TBW 1.0-1.1%, 0.8-0.9 kg, and for BF 1.2-1.6%, 1.1-1.3 kg depending on the analyzer used. CONCLUSIONS: The results of the present study demonstrate the stability of parameters of body composition throughout a working week, with the provision that standard measuring conditions are fulfilled. For the purpose of diagnostic practice, when interpreting the results of the repeated measurements, it is advisable to take as provable change caused by the observed factors only the ones whose values exceed the value of a weekly TE or the upper limit of the interval of the measurement reliability.
Keywords: Cohort Studies; Reproducibility of Results; mužské pohlaví; Young Adult; Body Composition; dospělí; Humans; Body Height; Adult; mladý dospělý; kohortové studie; reprodukovatelnost výsledků; tělesná hmotnost; tělesná výška; lidé; Male; Body Weight; složení těla